The psychoethics of syndemic: the pathic and the pathological - Lolas Stepke, Fernando (Acta Bioethica, 2020)
After discussing the scope and implications of the expression “mental health” at both the individual and social levels, this paper emphasizes that suffering (a pathic condition) is not always pathological in medical terms, and should be taken into consideration when evaluating the responses to the syndemic (the synergistic outcome of many alterations of the social milieu) caused by Covid19. Against the background of the historical-anthropological dimensions of experience and expectation of societies, the dialogical underpinning of bioethical thinking is rephrased as a psychoethics that incorporates an evaluation of the responses affecting the public, the communicators, and authorities. This reinforces the need for an empirical situationism in moral deliberation and the demand for empirical axiology in which judgments are made after continuous contrasting values, principles, and norms with the actual behavior of people.